The sibling effect on neurodevelopment of preschoolers under China’s newly relaxed child policy: A national retrospective cohort study - Dai, Xiaotian; Williams, Gareth; Lin, Senran; Baker, Charlie; Wu, Meiqin; Du, Wenchong; Hua, Jing (Frontiers in Psychology, 2022)
The change in Chinese fertility policy brings new challenges and considerations for children’s health outcomes, however, very little is known about the interaction between siblings, family socioeconomic status (SES), and neurodevelopment in the Chinese preschool-age population. Therefore, this study aimed to develop a new explanatory pathway from sibling effect to early childhood development and explored the mediation effect of family SES in the pathway. From April 2018 to December 2019, we conducted a national retrospective cohort study in 551 cities in China, and a total of 115,915 preschool-aged children were selected for the final analysis. Children’s neurodevelopment, including Communication, Gross motor, Fine motor, Problem-solving, and Personal-social, was assessed with the Ages & Stages Questionnaires, Third Edition (ASQ-3). Hypothesis tests and multilevel regression models were used to assess the associations and their strength between sibling effect and neurodevelopmental delay. Pathway analysis was used to verify the mediation effect of SES. The results showed that there were significant risk effects of a sibling on preschoolers’ overall neurodevelopment including communication, gross motor, fine motor, and problem-solving delay. The adjustment of family SES, however, brought a reversal of this association. The results of the mediation model illustrated a direct, protective effect of one-sibling status (βASQ-delay =-0.09; βASQ-scores=0.07; p<.001), and an indirect, risk effect from one-sibling status through family SES to neurodevelopment outcomes (βASQ-delay =0.12; βASQ-scores =-0.12; p<.001). The total sibling effect was weakened but remained negative (βASQ-delay =0.03; βASQ-scores =-0.05; p<.001). This study concluded that family SES mediated the negative effects of one sibling on early child development. To enhance the positive influence of sibling addition, we suggested providing more resources and instructions to the families with less educated and poorer employed parents under the coming multi-child era.